1968
DOI: 10.1113/expphysiol.1968.sp001984
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Fat Load on the Size and Composition of Chylomicrons in Thoracic Duct Lymph

Abstract: Chylomicrons of Sf 〉 400 and lipoproteins of Sf 12‐400 were separated by ultra‐centrifugation from samples of thoracic duct lymph collected from rabbits fed for 1 to 2 weeks previously on diets containing 5 per cent and 30 per cent corn oil or butter and from rats given a single intragastric dose of 0·5 ml. corn oil. The size of these particles after corn oil was determined by electron microscopy following fixation in osmium tetroxide. In rabbits on the low fat diet the mean diameter of chylomicrons was 960 Å … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

1969
1969
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 15 publications
4
21
1
Order By: Relevance
“…Smaller particles (such as VLDL) with a larger surface-to-volume ratio, would therefore be expected to contain relatively more protein, phospholipid, and cholesterol, and less triglyceride. Fraser, Cliff, and Courtice have also obtained evidence suggesting that differences in triglyceride-to-phospholipid ratios of thoracic duct lymph chylomicrons and VLDL can be explained by differences in particle size (33). The relative decrease in triglyceride content would in turn result in an increased particle density, while the relative increase in polar surface components could at least in part account for an increased electrophoretic mobility, Thus, several of the features which distinguish VLDL from chylomicrons could be explained solely on the basis of differences in particle size between the two lipoprotein classes.…”
Section: Discussionmentioning
confidence: 98%
“…Smaller particles (such as VLDL) with a larger surface-to-volume ratio, would therefore be expected to contain relatively more protein, phospholipid, and cholesterol, and less triglyceride. Fraser, Cliff, and Courtice have also obtained evidence suggesting that differences in triglyceride-to-phospholipid ratios of thoracic duct lymph chylomicrons and VLDL can be explained by differences in particle size (33). The relative decrease in triglyceride content would in turn result in an increased particle density, while the relative increase in polar surface components could at least in part account for an increased electrophoretic mobility, Thus, several of the features which distinguish VLDL from chylomicrons could be explained solely on the basis of differences in particle size between the two lipoprotein classes.…”
Section: Discussionmentioning
confidence: 98%
“…However, the amount of lipids transported during the postprandial state is severalfold greater than that transported during the fasting state. Increased transport of fat with similar amounts of apoB48 occurs because of an increase in the size of the particles during the postprandial state (42,43,54,63,72,173). Fat feeding also increases the expression of apoA-IV, which serves as a surface component for apoB48 particles in the enterocyte (77,135).…”
Section: Assembly Secretion and Regulation Of Intestinal Lipoproteinsmentioning
confidence: 99%
“…Zilversmit et al (1967) showed that in rabbits fed normal low fat diets, the lipids absorbed from the small intestines were also transported in lymph in the comparatively small lipoproteins. However, it was subsequently demonstrated that the sizes of these lymph lipoproteins were dependent on the amount of ingested dietary triacylglycerols and that the size increased with the intake of triacylglycerol (Fraser et al 1968;Ockner et al 1969;Fraser and Courtice 1969), accounting for the appearance of chylomicrons in plasma after the consumption of high fat diets (Simmonds 1972).…”
Section: Distribution Of Radioactivity In Lymph Lipoproteinsmentioning
confidence: 99%
“…The lymph sample remaining after removal of the chylomicrons was subjected to an 'infinite' ultracentrifugation at 100000 g at density 1·006 gil (Fraser et al 1968) to isolate the intestinal VLDL of All the samples of lymph lipoproteins were purified by washing through saline at density 1·006 gil for appropriate times in the ultracentrifuge and reconstituted to their original volume (Fraser 1970).…”
Section: Preparative Ultracentrifugationmentioning
confidence: 99%
See 1 more Smart Citation